Analisis Kapasitas Tampang Sungai Jambo Balee Terhadap Banjir Periode Ulang - Bayu Surahman Prasetyo Manik; Ichsan Syahputra; Muhammad Zardi (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Indra Makmur Sub-District floods frequently occur every year, the flood originates from the overflow of the Jambo Balee river in the area. The watershed (DAS) in the area flows through residential areas in Jambo Balee Village, Indra Makmur sub-district, East Aceh district. The research objective was to determine the flood discharge, flood water level, and capacity of the Jambo Balee River. So the research carried out was to analyze hydrology and hydraulics regarding the study of the planned flood discharge in the Jambo Balee watershed area. The analysis was carried out by looking for the design rainfall using the Pearson III Log distribution that meets the criteria in the calculation of statistical parameters. The rain data used comes from malikussaleh station. The rainfall data used is maximum daily rainfall data from 2012 to 2021. Flood discharge analysis uses the HSS Nakayasu and HSS Gama I methods. In the hydraulics analysis the method used is HSS Nakayasu. The HSS Nakayasu flood discharge data is used as input in the cross-sectional profile modeling in the HEC-RAS software. The results of the flood discharge analysis using the HSS Nakayasu method for return periods of 2, 5, 10, 25, 50, 100 years, respectively are 79,129 m3/s, 108,045 m3/s, 125,340 m3/s, 145,290 m3/s, 158,916 m3/s sec, and 171,567 m3/s. From the results of the hydraulic analysis, the simulation results show that with a return period of 10, 25, 50, and 100 years, the river surface overflows. At STA 0+250 HU it can be seen that the flood water level for the 10 year return period is at a height of 3 m and for the 25 year return period is at a height of 3.5 m. Therefore, the Jambo Balee River cannot accommodate the flood discharge that occurs.